모디 정부 하의 인도-미국 관계 변화 및 외교전략 분석 (2014~2024) - 박혜성(Park, Hye-Sung); 지연정(Ji, Yeon-Jung) (남아시아연구, 2024)
이 연구는 모디 정부 하에서 인도-미국 관계의 형성과 발전을 분석하였다. 분석은 국방과 경제 분야를 중심으로 하였으며, 우주 및 에너지 분야의 협력도 검토하였다. 또한 러시아-우크라이나 전쟁, 이란과 파키스탄 관련 문제, 무역 갈등 등 양국 관계를 저하시키는 정책 및 사건을 다룸으로써 인도와 미국 관계의 구체적인 변화를 파악하고자 하였다. 분석 결과, 모디 정부 하에서 인도와 미국의 관계는 대화 채널 구축, 광범위한 정보 공유, 무역 문제 해결 노력 측면에서 상당한 개선을 보였다. 그러나 관계 발전 과정에서 양국의 이익 충돌 지점도 명확해졌으며, 각국은 여전히 자국의 외교 및 경제적 입장을 유지하고 있다. 특히 국제적 갈등, 지역 안보 문제, 지적 재산권 및 디지털 경제 등의 사안에서 양국 간 입장 차이가 두드러졌다. 모디 정부는 미국과의 협력을 통해 인도의 안보 및 경제적 역량을 강화시키면서도 비서방 국가들과의 협력을 유지하며 전략적 선택지를 확대하고자 하였다. 또한 다양한 다자기구에 참여하여 인도의 글로벌 리더십을 강화하려는 노력을 병행하였다. 이러한 접근은 인도의 장기적 경제 및 안보 이익을 확보하고 외교적 자율성을 증대시키기 위한 모디 정부의 전략적 방향성을 보여준다. This paper analyzes how India-U.S. relations have been shaped, developed, and settled under the Modi government from 2014 to 2024. In a review of bilateral relations, we conducted a analysis by categories mainly in the fields of defense and economic relations. Additionally, we reviewed the India-U.S. space and energy sectors as part of the improvement of bilateral relations. We also considered degrading factors for these relations, including the Russia-Ukraine War, issues concerning Iran and Pakistan, and trade conflicts. After careful examination, we reached three conclusions. First, India-U.S. relations have made historical improvements in all domains in terms of building communication channels, sharing a wide range of information, and resolving decade-old trade issues. However, the two countries still maintain separate diplomatic and economic stances when their national interests conflict. Emerging issues include divergent positions on internaitonal conflicts, regional issues, intellectual property, and the digital economy. While these disagreements keep the two countries from reaching full compromise, India-U.S. relations are clearly developing toward a convergence of interests, forging a strategic space for each other by connecting with one another. KCI Citation Count: 0